2022
DOI: 10.1017/s2045796022000026
|View full text |Cite
|
Sign up to set email alerts
|

Housing First for homeless people with severe mental illness: extended 4-year follow-up and analysis of recovery and housing stability from the randomizedUn Chez Soi d'Abordtrial

Abstract: Aims Housing First (HF), a recovery-oriented approach, was proven effective in stabilising housing situations of homeless individuals with severe mental disorders, yet had limited effectiveness on recovery outcomes on a short-term basis compared to standard treatment. The objective was to assess the effects of the HF model among homeless people with high support needs for mental and physical health services on recovery, housing stability, quality of life, health care use, mental symptoms and addiction iss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…Housing related outcomes were most reported, with studies reporting positive housing-related effects. Improvements in quality of life were reported in six studies [ 30 , 33 , 38 , 51 , 54 , 65 ], and improvements in mental health [ 51 , 54 , 55 ], and income [ 34 , 52 , 66 ] were reported in three studies each.…”
Section: Resultsmentioning
confidence: 99%
“…Housing related outcomes were most reported, with studies reporting positive housing-related effects. Improvements in quality of life were reported in six studies [ 30 , 33 , 38 , 51 , 54 , 65 ], and improvements in mental health [ 51 , 54 , 55 ], and income [ 34 , 52 , 66 ] were reported in three studies each.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies emanated from Norway ( 11 , 12 , 19 , 20 , 34 ), two from Belgium ( 22 , 36 ), and a third based on data from Belgium and the Netherlands ( 17 ). Two studies originated in Australia ( 27 , 38 ), while single studies emerged from France ( 32 ), Canada ( 29 ), Denmark ( 28 ) and Sweden ( 21 ). A third of the studies (n=8) addressed substance use recovery while two-thirds (n=17) addressed co-occurring disorders.…”
Section: Resultsmentioning
confidence: 99%
“…The one randomized control trial included in this review focused on homeless individuals with mental health disorders ( 32 ). Follow-up of the sample revealed improvements in personal recovery outcomes, higher housing stability, independence, and lower use of hospital services compared to the treatment-as-usual group, but, enduring issues with alcohol ( 32 ). Findings speak to the long-term benefits of this intervention for this population.…”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant changes found between the two groups over time after application of intervention. (48) Moreover, the study conducted by Jensen S. et al (2021) whose examined the effectiveness of their recovery program for people with SMIs as schizophrenia and revealed that no significant differences between the recovery group and the control groups in terms of recovery and all areas of psychological difficulties. (49) Vol.…”
Section: Discussionmentioning
confidence: 99%